2008
DOI: 10.1029/2007jg000542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the chemical alteration trajectory of Liriodendron tulipifera L. leaf litter among forests with different earthworm abundance

Abstract: [1] To investigate the control of earthworm populations on leaf litter biopolymer decay dynamics, we analyzed the residues of Liriodendron tulipifera L. (tulip poplar) leaves after six months of decay, comparing open surface litter and litter bag experiments among forests with different native and invasive earthworm abundances. Six plots were established in successional tulip poplar forests where sites varied in earthworm density and biomass, roughly 4-10 fold, of nonnative lumbricid species. Analysis of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 74 publications
2
53
0
Order By: Relevance
“…The uncut forests are dominated by several species of oak (Quercus) with the dominant species being chestnut oak (Q. prinus) which contributes 70% of the total litter input (Szlavecz unpublished data). Previous research by our group has demonstrated that nonnative earthworms are an important component of SERC forests (Crow et al, 2009;Filley et al, 2008;Ma et al, 2013;Szlavecz and Csuzdi, 2007;Szlavecz et al, 2011). In the context of this study, the uncut forests on Hog Island, Fox Point and Big Island are earthworm-free while non-native earthworms are abundant in soils at the old and young forest stands (Szlavecz and Csuzdi, 2007;Szlavecz et al, 2011).…”
Section: History and Description Of The Smithsonian Environmental Resmentioning
confidence: 79%
See 2 more Smart Citations
“…The uncut forests are dominated by several species of oak (Quercus) with the dominant species being chestnut oak (Q. prinus) which contributes 70% of the total litter input (Szlavecz unpublished data). Previous research by our group has demonstrated that nonnative earthworms are an important component of SERC forests (Crow et al, 2009;Filley et al, 2008;Ma et al, 2013;Szlavecz and Csuzdi, 2007;Szlavecz et al, 2011). In the context of this study, the uncut forests on Hog Island, Fox Point and Big Island are earthworm-free while non-native earthworms are abundant in soils at the old and young forest stands (Szlavecz and Csuzdi, 2007;Szlavecz et al, 2011).…”
Section: History and Description Of The Smithsonian Environmental Resmentioning
confidence: 79%
“…While agricultural legacies are still detected in old forest soils, present nutrient concentrations may be more strongly affected by the ongoing mixing of leaf litter with mineral soil. Detailed chemical analyses of plant litter residue and different fractions of soil organic matter at a subset of our sites strongly support the latter mechanism (Filley et al, 2008;Crow et al, 2009;Ma et al, 2013).…”
Section: Organismsmentioning
confidence: 90%
See 1 more Smart Citation
“…Filley et al [65] determined the use of 1 mm mesh litterbags was sufficient to exclude all macrofauna in their study including earthworms in northern temperate deciduous forests on a successional spectrum. In a comparison study between Northern deciduous and conifer forests in Colorado, González et al [63] used litterbags of two different mesh sizes to quantify the effects of different groups of soil fauna on the decay of aspen leaves and lodgepole pine needles.…”
Section: Litterbagsmentioning
confidence: 99%
“…Comparing mass loss rates between different mesh size leaf litterbags or between earthworm treatments may allow deduction of the direct influence of the given earthworm community on these processes [45,[62][63][64][65][66][67].…”
Section: Leaf Litter Consumptionmentioning
confidence: 99%